Pharmacokinetics and Safety of Intravenous Ceftolozane-Tazobactam in Healthy Adult Subjects following Single and Multiple Ascending Doses - Miller, Benjamin; Hershberger, Ellie; Benziger, David; Trinh, MyMy; Friedland, Ian (Antimicrobial Agents and Chemotherapy, 2012)
The pharmacokinetics and safety of ceftolozane, a novel cephalosporin, and tazobactam, a β-lactamase inhibitor, alone and in combination as a 2:1 ratio in single doses of up to 2,000 and 1,000 mg of ceftolozane and tazobactam, respectively, and multiple doses of up to 3,000 and 1,500 mg of ceftolozane and tazobactam, respectively, per day were evaluated in healthy adult subjects. In part 1, groups of six subjects each received single ascending doses of ceftolozane, tazobactam, and ceftolozane-tazobactam in a within-cohort crossover design. In part 2, groups of 5 or 10 subjects each received multiple doses of ceftolozane, tazobactam, or ceftolozane-tazobactam for 10 days. After a single dose of ceftolozane alone, the ranges of mean values for half-life (2.48 to 2.64 h), the total clearance (4.35 to 6.01 liters/h), and the volume of distribution at steady state (11.0 to 14.1 liters) were consistent across dose levels and similar to those observed when ceftolozane was coadministered with tazobactam. Mean values after multiple doses for ceftolozane alone and ceftolozane-tazobactam were similar to those seen following a single dose. The pharmacokinetics of the dosing regimens evaluated were dose proportional and linear. Ceftolozane-tazobactam was well tolerated and systemic adverse events were uncommon. Mild infusion-related adverse events were the most commonly observed following multiple-dose administration. Adverse events were not dose related, and no dose-limiting toxicity was identified.